The influence of age on the prevalence of inflammatory and structural MRI lesions in the sacroiliac joints of patients with and without axial spondyloarthritis. (9th September 2022) - Baraliakos, Xenofon; Kuehn, Anna; Tsiami, Styliani; Kiltz, Uta; Fruth, Martin; Braun, Juergen
Abstract: Objectives: To compare the influence of age on inflammatory (bone marrow oedema [BME]) and structural (fat lesions [FL], erosions and ankylosis) MRI lesions in the sacroiliac joints (SIJ) of patients with and without axial spondyloarthritis (axSpA). Methods: In a retrospective study, SIJ MRI (STIR/T1 sequences) of consecutive patients with chronic back pain diagnosed with axSpA or non-SpA were evaluated based on SIJ quadrants (SIJ-Q). Two blinded readers evaluated BME and structural lesions. Reader agreement was evaluated for prevalence of MRI lesions related to age. Results: MRIs of 309 (175 axSpA, 134 non-SpA) patients were evaluated. Their mean age was 38.5 (11.4) and 43.4 (13.8) years, 67% and 36% were male, CRP was 1.6 (2.4) and 1.1 (2.1) mg/dl and median symptom duration was 48 and 60 months for axSpA and non-SpA, respectively. SIJ-Q with BME and erosions were significantly more frequent in axSpA vs non-SpA patients independent of age, while this difference was seen for FL only in patients ≥50 years. The proportion of patients with ≥1 or ≥3 BME or chronic lesions except for FL increased with age in both groups, and was constantly higher in axSpA vs non-SpA. In univariate analyses, only female sex was significantly associated with more FL. Conclusions: The proportion of patients with MRI lesions was high in both axSpA and non-SpA patients. However, the prevalence of BME and erosions was significantly more frequent in patients with axSpA, was independent of age and also allowed for discrimination. FL occurred more frequently only in older age groups and were less reliable for discrimination vs non-SpA patients.